Legal Framework for Resolving Local Government Loan Defaults in Indonesia: A Comparative Study of Positive and Islamic Law - Samsul Arifin; FX Sumarja; Sunaryo Sunaryo; Agus Triono (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study critically analyzes the legal framework for resolving local government loan defaults in Indonesia through a comparative lens between positive law and Islamic law. It aims to identify both normative and practical shortcomings in the current regulatory mechanisms while proposing a more equitable, sustainable, and ethically grounded legal solution. Employing a normative juridical method with statutory and conceptual approaches, the research is analyzed qualitatively based on the principles of justice, the rule of law, and Islamic legal doctrines. The findings indicate that Law No. 1 of 2022 disproportionately places the burden of loan default risks on local governments without adequate consideration of the fiscal disparities among regions. Moreover, the absence of a clear mechanism for resolving defaults outside the central government’s domain creates legal uncertainty for creditors and disrupts the delivery of public services. From the perspective of Islamic law, the current framework neglects core principles such as ‘adl (justice), maslahah (public interest), and raf’ al-ḍarar (harm prevention), which emphasize fairness, debt restructuring, and social responsibility. The study recommends a hybrid approach that integrates positive legal reforms, such as amendments to Law No. 1/2022 and the application of the Suspension of Debt Payment Obligations (PKPU), with Islamic dispute resolution models like sulh (amicable settlement) and tahkīm (arbitration). The academic contribution of this study lies in its interdisciplinary framework that bridges conventional legal analysis with Islamic jurisprudence, offering a novel perspective on fiscal legal governance in decentralized states. This research enriches the scholarly discourse on legal pluralism, fiscal justice, and the contextual application of Islamic legal principles in modern governance structures, particularly in managing local government financial obligations